Al-Mawād at-Ta‘līmīyyah ‘alā Asās al-Kifāyah al-Ittiṣāliyyah fī al-Kitāb al-Madrasī “Al-‘Arabiyyah al-Mu‘āṣirah” li Eckehard Schulz - Musyrifa, Furaida Ayu; Wargadinata, Wildana; Ifawati, Nur Ila; Luthfi, Khabibi Muhammad (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2021)
Abstract One of the textbooks used in different countries written by non-Arabs is